Cost analysis of coral gardening in bato bukay MPA, Guimbal, Iloilo. - Acob, Philina Riva L.
This study analyzes the costs of coral gardening in Bato Bukay MPA in Guimbal, Iloilo. Cognizant of the degradation of their coastal areas and fisheries, the community of Brgy. Nalundan, where the marine protected area is located, sought to find solution through marine conservation and coral gardening. Being the habitat and breeding grounds of fishes, coral reefs are one of the most important natural resources that people must protect. Hence, several projects were implemented to propagate the establishment of Marine Protected Areas such as the deployment of artificial reefs and coral gardening activities. Costs of coral gardening in the site were estimated using key informant interviews with individuals who were involved with or who were knowledgeable on the establishment and maintenance of the project, and from secondary sources, thereby enabling the computation of the total costs. A survey of randomly selected participants that included Contingent Valuation Method was conducted in barangays Nalundan, Calampitao and Cabubugan, to determine the socio-economic profile and estimate the local community support through their willingness-to-pay and willingness to support in kind. Proportional sampling formula, adjusted to small population was used to determine the number of these participants across the barangays. The total cost for coral gardening on its first year was estimated as Php 336, 684 combining all the fixed, variable and opportunity costs incurred. Out of the total costs, 40% amounted as fixed costs, while 33% were variable costs, and 27% constituted opportunity costs. More people were willing to pay in-kind by volunteering than to pay in monetary terms for the project?s fund for sustainability.